2015
DOI: 10.1186/s13104-015-1307-5
|View full text |Cite
|
Sign up to set email alerts
|

The burden among family caregivers of elderly cancer patients: prospective study in a Moroccan population

Abstract: BackgroundIn Morocco, families play a major role in caring for elderly cancer patients.MethodsWe conducted a prospective descriptive study, in the National Institute of Oncology in Morocco. The study aimed to include family members who are caregivers for patients aged ≥70 years old.FindingsAfter obtaining IRB approval, a total of 150 caregivers responded to the questionnaire. Mean age was 44.7 years. The majority were females (59.3%), living in urban areas (66.7%), and educated (62.7%).Offspring (sons or daugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
(23 reference statements)
3
26
0
8
Order By: Relevance
“…This psychological burden is not peculiar to family caregivers in Enugu urban. Similar studies in Nigeria (Ebimgbo et al, 2019;Ogunmodede et al, 2019) and Morocco (Lkhoyaali, et al, 2015) found that family caregivers underwent tremendous stress, psychological distress, depression and extreme anxieties while giving care to the elderly.…”
Section: Discussionsupporting
confidence: 55%
“…This psychological burden is not peculiar to family caregivers in Enugu urban. Similar studies in Nigeria (Ebimgbo et al, 2019;Ogunmodede et al, 2019) and Morocco (Lkhoyaali, et al, 2015) found that family caregivers underwent tremendous stress, psychological distress, depression and extreme anxieties while giving care to the elderly.…”
Section: Discussionsupporting
confidence: 55%
“…- In the Moroccan context, it is usual for the family to ask the doctor to hide the diagnosis of cancer from the patient [14], so we included this question in the questionnaire.…”
Section: Socio-demographic and Economic Datamentioning
confidence: 99%
“…The results on depression also vary. Almost one-quarter of family caregivers participating in study of Lkhoyaali et al (2015) were depressed. Another study showed that the caregivers scored considerably higher on depression compared to the UK adult general population sample with almost one-quarter of all these caregivers being moderately, severely or even extreme severely depressed (Kurtz et al, 2004).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Depression was measured with: DSM-IV(Lkhoyaali et al, 2015), the depression subscale of the Depression Anxiety Stress Scale (DASS21)(Jones et al, 2015), the Geriatric Depression Scale (5-item GDS)(Goldzweig, Baider, Andritsch, & Pfeffer, 2016) and (a subscale of) the Center for Epidemiological Studies Depression Scale (CES-D)(Bachner et al, 2009;Kurtz, Kurtz, Given, & Given, 2004;Raveis et al, 1998). All of the above are validated scales except the DSM-IV.…”
mentioning
confidence: 99%